Study of In-Cylinder Heat Transfer Boundary Conditions for Diesel Engines Under Variable Altitudes Based on the CHT Model - Zhang, Yu; Yan, Yuchao; Yang, Ruomiao; Wang, Qifan; Zhang, Bowen; Gan, Qingliang; Liu, Zhentao; Fu, Jiahong (Frontiers in Energy Research, 2022)
The reliability of combustion chamber components is determined by thermal load of diesel engines. It was found that a great decrement of diesel engine performance and the ablation area on the surface of cylinder head and piston when vehicles drove from plain to plateau area, which was largely due to significant increment of prediction error using Woschni formula at high altitudes. The objective of this study was to propose an improved model to increase model predicting accuracy at various altitudes. A modified conjugate heat transfer (CHT) model of combustion chamber and cooling medium was proposed to analyze the temperature field distribution of cylinder head at different altitudes. The results indicated that relative errors were controlled within 5% under variant altitudes, comparing the temperature field of numerical simulation with the single-cylinder engine experiment test data. Therefore, the in-cylinder heat transfer model can be used to predict the thermal load of diesel engine combustion chamber components under different altitude operating conditions.